Feeding behavior and preference of horses fed rhizome peanut hay - Cerqueira de Melo Vasco, Ana Caroline (2021)
Rhizoma peanut (RP, Arachis glabrata Benth) has been used as alternative legume hay for horses; however, feeding behavior and preference of horses fed this hay in comparison to other commonly fed hays war- rant investigation. This study aimed to evaluate the feeding behavior and preference of mature horses with maintenance requirements fed RP “Florigraze”hay compared with alfalfa (ALF, Medicago sativa L. “Legendary XHD”) and bermudagrass (BMG, Cynodon dactylon L. “coastal”) hays. Six mature Quarter Horse geldings (593 ±40 kg; mean ±SD) were used in a replicated 3 ×3 Latin square with 21-day pe- riods. Horses were individually housed in 5 ×4 m stalls bedded with wood shavings. Hays were offered to horses in 46 ×36 cm 66-L rubber-polyethylene containers. Hays were analyzed for chemical composi- tion before the start of the study. After a 14-day diet adaptation, 24-hour behavioral observations were conducted using scan sampling. Time spent feeding, inactive, and at other activities were recorded every 10 minutes. Three-choice preference tests were conducted for a 2-hour duration twice daily on day 20 and 21 by simultaneously presenting 1 kg (as-fed basis) of all 3 hays. Horses’ first choice, hay consump- tion, and number of times each hay was smelled or tasted but left in preference for another hay were recorded. Preference data were analyzed using descriptive statistics, while behavioral data and hay con- sumption were analyzed using repeated measures mixed model ANOVA. A hay x time-of-day effect was observed on feeding time ( P = 0.0408), and ALF resulted in reduced feeding time 2-4 hours after meals were offered compared to RP and BMG. Daily feeding time was shorter ( P < 0.0 0 01) with ALF than BMG (11.7 vs. 8.9 h/d), but RP (9.9 h/d) did not differ from BMG or ALF. Total daily inactivity time was greatest for ALF ( P = 0.0037) and similar between BMG and RP. Hay consumption was greatest ( P < 0.0 0 01) for ALF (0.996 ±0.015 kg as-fed/test; mean ±SE), followed by RP (0.935 kg), and least with BMG (0.792 kg). Horses show preference for legumes over grass hay, which might be associated with the higher protein and energy and lower fiber concentration of the hays. Rhizoma peanut has the potential to provide im- proved welfare by providing decreased inactivity time compared to ALF, while being preferred over BMG. These attributes make RP a suitable forage source for horses.